2020
DOI: 10.1039/d0cc05492e
|View full text |Cite
|
Sign up to set email alerts
|

Selective functionalization at N2-position of guanine in oligonucleotides via reductive amination

Abstract: Chemo- and site-specific modifications in oligonucleotides have wide applicability as mechanistic probes in chemical biology. However, methods that label specific sites in nucleic acids are scarce, especially for labeling DNA/RNA...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…The position at N 2 was chosen because guanine can be naturally modified at N 2 , [25] and it has prevously been shown that N 2 modifications do not hinder enzymatic digestion. [26] The modifed G35 nucleoside was then linked to Lac azide or alternatively to Neu5Ac-Lac azide via copper promoted azide-alkyne cycloaddition, leading to their respective conjugates (Y5 RNA-Lac and Y5 RNA-Neu5Ac-Lac) (Scheme 1). Using a denaturing gel, a clear shift was observed after conjugation of the Lac and Neu5AcLac (Figure 1 Panel A).…”
Section: Conjugation Of Glycans To Synthetic Y5 Rna and Chemical Anal...mentioning
confidence: 99%
“…The position at N 2 was chosen because guanine can be naturally modified at N 2 , [25] and it has prevously been shown that N 2 modifications do not hinder enzymatic digestion. [26] The modifed G35 nucleoside was then linked to Lac azide or alternatively to Neu5Ac-Lac azide via copper promoted azide-alkyne cycloaddition, leading to their respective conjugates (Y5 RNA-Lac and Y5 RNA-Neu5Ac-Lac) (Scheme 1). Using a denaturing gel, a clear shift was observed after conjugation of the Lac and Neu5AcLac (Figure 1 Panel A).…”
Section: Conjugation Of Glycans To Synthetic Y5 Rna and Chemical Anal...mentioning
confidence: 99%
“…This mild reducing agent selectively reduces imines over unreacted aldehydes at pH 6. [20] NaBH 3 CN was used for a variety of chemical reductions especially for bioconjugation. [21] For the reaction in presence of a template strand, the complementary sequence to ODN1 contained a natural nucleobase opposite to the amino site (T C , T G , T A , T T : 5'-CGCTATY-TATCGC, where Y=C, G, A, T; Table 1).…”
Section: Chembiochemmentioning
confidence: 99%
“…The overall method involves protection at the N 9 position of the guanine, alkylation at the N 2 position, and then deprotection to afford the corresponding N 2 ‐alkylguanine. The most reliable method for the synthesis of N 2 ‐ alkyl guanosine involves the condensation between the exocyclic amine of guanosine and the aldehyde, followed by sodium cyanoborohydride reduction (Sako et al., 1999; Bhoge et al., 2020). In addition to the use of sodium cyanoborohydride, sodium borohydride was used as a reducing agent for the reaction between guanosine and the aldehyde to afford the corresponding N 2 ‐ alkyl guanosine (Kemal & Reese, 1980).…”
Section: Commentarymentioning
confidence: 99%